Tourism, cultural activities and sustainability in the Spanish Mediterranean regions: a probit approach - Andres Artal-Tur; Antonio Juan Briones-Peñalver; Marina Villena-Navarro (Tourism & Management Studies)
Culture is the preferred activity of sun & sand tourists visiting the Spanish Mediterranean regions. Improving our knowledge on the factors surrounding this type of demand appears to be pivotal for the continuous renewal of those mature destinations. With this objective we apply probit models to a data set of more than 200,000 questionnaires accounting for the socio-economic characteristics of the tourists, their trip behaviour, and destination and time fixed effects. Results allow us to identify interesting characteristics of tourism and of cultural activities, making this product a